2010
DOI: 10.1152/ajpendo.00239.2009
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle glucose uptake during contraction is regulated by nitric oxide and ROS independently of AMPK

Abstract: Merry TL, Steinberg GR, Lynch GS, McConell GK. Skeletal muscle glucose uptake during contraction is regulated by nitric oxide and ROS independently of AMPK. Am J Physiol Endocrinol Metab 298: E577-E585, 2010. First published December 15, 2009; doi:10.1152/ajpendo.00239.2009.-Reactive oxygen species (ROS) and nitric oxide (NO) have been implicated in the regulation of skeletal muscle glucose uptake during contraction, and there is evidence that they do so via interaction with AMP-activated protein kinase (AMPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 57 publications
(101 reference statements)
5
97
5
Order By: Relevance
“…These conclusions are consistent with previous studies in which AMPK␣ 2 was shown to be a necessary signal in the regulation of substrate metabolism during muscle contraction or treadmill exercise (24,25). However, our data are not consistent with some additional reports in which low AMPK␣ 2 activity did not affect muscle glucose clearance during treadmill exercise (26), glucose uptake in contracting extensor digitorum longus muscle, which is a mixed-fiber type muscle (10), or FA oxidation in isolated muscle during muscle contraction or following treadmill exercise (4,10,25,29,30). Possible explanations for these differences include the fact that the exercise mode and the fiber types were different between studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These conclusions are consistent with previous studies in which AMPK␣ 2 was shown to be a necessary signal in the regulation of substrate metabolism during muscle contraction or treadmill exercise (24,25). However, our data are not consistent with some additional reports in which low AMPK␣ 2 activity did not affect muscle glucose clearance during treadmill exercise (26), glucose uptake in contracting extensor digitorum longus muscle, which is a mixed-fiber type muscle (10), or FA oxidation in isolated muscle during muscle contraction or following treadmill exercise (4,10,25,29,30). Possible explanations for these differences include the fact that the exercise mode and the fiber types were different between studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Force production measurements were made in anesthetized WT and DN mice to determine whether AMPK␣ 2 deficiency would affect (10) or not affect (29) force production with this protocol (13,14). The right tibiopatellar ligament was stabilized for the recording of force production, and a modular chart recorder (Cole Parmer, Vernon Hills, IL) was used to measure the tension developed by the GSP muscle group during the 20-min muscle stimulation protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Of many intracellular ROS production mechanisms, the mitochondrion is the most prominent ROS generator wherein constitutive ROS production arises from leakage of a small percent of electrons from the electron transfer chain (ETC) [7,8]. In skeletal muscle, which requires high energy supply and contains abundant mitochondria, adequate amount of ROS modulates muscle contractility and glucose metabolism [9,10], while excessive ROS is responsible for muscle fatigue and insulin resistance [1,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This dual signaling input for contraction-induced GLUT4 translocation is in line with studies in skeletal muscle demonstrating that AMPK is essential but not sufficient for contraction-induced GLUT4 translocation and glucose uptake (25,26). On the other hand, another study in skeletal muscle showed that contraction-induced GLUT4 translocation was found to be dependent on ROS signaling and independent of AMPK activation (21). Hence, further studies are needed to study the combined roles of ROS and AMPK signaling in skeletal muscle.…”
mentioning
confidence: 99%
“…Namely, it has been shown that the induction of contraction enhances ROS formation in cardiomyocytes (20) and that ROS scavengers inhibit contractioninduced glucose uptake (21,22). Furthermore, PKD1 is known to be activated by mitochondrial ROS (9).…”
mentioning
confidence: 99%